1991
DOI: 10.1044/jshr.3406.1222
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Coarticulation in the Speech of Adults and Young Children

Abstract: Three experiments investigated anticipatory lingual and labial coarticulation in the [sV] productions of children and adults. Acoustic, perceptual, and video data were used to trace the development of intrasyllabic coarticulation in the speech of adults and children (ages 3, 5, and 8 years). Although children show greater variability in their articulatory patterns than adults, the data do not support claims that young children produce a greater degree of intrasyllabic coarticulation than older children or adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
1
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 34 publications
9
53
1
3
Order By: Relevance
“…Our findings can be compared with the results of these acoustic analyses, because it has been claimed that F2 anticipation represents lingual coarticulatory effects, as opposed to lip rounding ( [6], p. 122). Two studies, [9] and [3], found no significant differences in coarticulation between children and adults; [6] showed greater coarticulation in children. Slight methodological differences between these works could have contributed to the conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings can be compared with the results of these acoustic analyses, because it has been claimed that F2 anticipation represents lingual coarticulatory effects, as opposed to lip rounding ( [6], p. 122). Two studies, [9] and [3], found no significant differences in coarticulation between children and adults; [6] showed greater coarticulation in children. Slight methodological differences between these works could have contributed to the conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies ( [9,6,3]) analysed coarticulatory effects produced by the vowels /i/ and /u/ on coronal consonants, by measuring the concentration of energy during the consonant in anticipation of the vowel F2. Our findings can be compared with the results of these acoustic analyses, because it has been claimed that F2 anticipation represents lingual coarticulatory effects, as opposed to lip rounding ( [6], p. 122).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated age-related differences in the extent and degree of coarticulation (e.g., Repp, 1986;Hodge, 1989;Nittrouer, Studdert-Kennedy & McGowan, 1989;Katz, Kripke, & Tallal, 1991). These studies have demonstrated mixed results concerning whether children show greater, less or equal gestural overlap than adults.…”
Section: Chapter 1 Introductionmentioning
confidence: 97%
“…Several studies reported that children exhibit a greater degree of anticipatory coarticulation than adults (Repp, 1986;Nittrouer & Whalen, 1989;Ha & Kuehn, 2006), while other studies indicate that children have less coarticulation than adult speakers (Thompson & Hixon, 1979;Hodge, 1989). A third set studies reported that adults and children exhibit approximately the same amount of coarticulation, yet children exhibited increased variability in their coarticulation (Turnbaugh, Hoffman, & Daniloff, 1985;Sereno, Baum, Marean, & Lieberman, 1987;Katz, Kripke, & Tallal, 1991;Goodell & Studdert-Kennedy, 1993;Katz & Bharadwja, 2001). Regardless of whether children show equal, greater or less gestural overlap compared to adults' speech, the differences between adults and children may provide valuable information about child's articulatory timing control.…”
Section: Developmental Patterns Of Coarticulationmentioning
confidence: 99%
See 1 more Smart Citation